Light extraction from solution-based processable electrophosphorescent organic light-emitting diodes - Choulis, Stelios A.; Krummacher, Benjamin C.; Mathai, Mathew K. (My University, 2007)
Molecular dye dispersed solution processable blue emitting organic light-emitting devices have been fabricated and the resulting devices exhibit efficiency as high as 25 cd/A. With down-conversion phosphors, white emitting devices have been demonstrated with peak efficiency of 38 cd/A and luminous efficiency of 25 lm/W. The high efficiencies have been a product of proper tuning of carrier transport, optimization of the location of the carrier recombination zone and, hence, microcavity effect, efficient down-conversion from blue to white light, and scattering/isotropic remission due to phosphor particles. An optical model has been developed to investigate all these effects. In contrast to the common misunderstanding that light out-coupling efficiency is about 22% and independent of device architecture, our device data and optical modeling results clearly demonstrated that the light out-coupling efficiency is strongly dependent on the exact location of the recombination zone. Estimating the device internal quantum efficiencies based on external quantum efficiencies without considering the device architecture could lead to erroneous conclusions
Keywords: Dyes and dyeing; Phosphorescence; Phosphors; Light--Scattering